Chromatin as active matter. (13th January 2017) - Agrawal, Ankit; Ganai, Nirmalendu; Sengupta, Surajit; Menon, Gautam I
Abstract: Active matter models describe a number of biophysical phenomena at the cell and tissue scale. Such models explore the macroscopic consequences of driving specific soft condensed matter systems of biological relevance out of equilibrium through 'active' processes. Here, we describe how active matter models can be used to study the large-scale properties of chromosomes contained within the nuclei of human cells in interphase. We show that polymer models for chromosomes that incorporate inhomogeneous activity reproduce many general, yet little understood, features of large-scale nuclear architecture. These include: (i) the spatial separation of gene-rich, low-density euchromatin, predominantly found towards the centre of the nucleus, vis a vis . gene-poor, denser heterochromatin, typically enriched in proximity to the nuclear periphery, (ii) the differential positioning of individual gene-rich and gene-poor chromosomes, (iii) the formation of chromosome territories, as well as (iv), the weak size-dependence of the positions of individual chromosome centres-of-mass relative to the nuclear centre that is seen in some cell types. Such structuring is induced purely by the combination of activity and confinement and is absent in thermal equilibrium. We systematically explore active matter models for chromosomes, discussing how our model can be generalized to study variations in chromosome positioning across different cell types. The approach and model we outline here represent a preliminary attempt towards a quantitative, first-principles description of the large-scale architecture of the cell nucleus.